Lombardy Region: seven years of breast cancers screening before, during and after the SARS-CoV-2 pandemic - Ticozzi, Elena Maria; Perrone, Pier Mario; Deandrea, Silvia; Tanious, Marina; Cereda, Danilo; Castaldi, Silvana (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Breast cancer represents the most common form of neoplasm in women, with an estimated 685,000 deaths annually. In this regard, screening programmes represent one of the most effective intervention tools in the field of cancer prevention. The aim of this study is to analyse and describe the key performance indicators of the screening programmes in Lombardy from 2016 to 2022. Study design. Descriptive temporal analysis study. Methods. The data pertaining to the screening campaign were subjected to analysis, with the results broken down according to the following criteria: individual province, age group eligible for screening, and campaign year. For each campaign, the data pertaining to the population subjected to screening, as well as the data concerning the rate of cancers identified during the campaign, were subjected to analysis. Results. For the three age groups, a substantial overlap in call and campaign adherence rates can be observed, with stable values between 2016 and 2019, followed by a significant decline in the 2020 campaign associated with the impact of the pandemic on prevention activities, including cancer screening campaigns. The data for 2021 and 2022 indicate a reversal of the decline in adherence and call rates, particularly in the 45–49 age group, which exhibited an increase of approximately 300% in the call rate between 2021 and 2020. Moreover, the categorization of the provinces into urban, mountainous and rural provinces demonstrates an overlap in the admission rates between the three areas in the different years. Conclusions. Despite the existence of mammography screening campaigns for more than 20 years, adherence rates in the Lombardy region remain below the targets set out in Europe’s Beating Cancer Plan. In this regard, the observed variations, particularly during the period of the pandemic and in the subsequent post-pandemic period, provide an opportunity to rethink the organization of screening campaigns in order to increase adherence and effectiveness.